MODELING AND RESEARCH OF PROCESSES FOR CREEP COMPLIANCE AND RELAXATION BASED ON FADING MEMORY CONCEPT (Journal of Mathematics Mechanics and Computer Science, 2023)
Using of rheonomic materials in engineering structures is one of the most important issues in determining strength and durability. The main task of the mechanics of a deformable solid is to simulate the processes of deformation of viscoelastic materials. Currently, there are quite well-developed theories and methods of viscoelasticity that allow to determine and describe the viscoelastic properties of materials. They differ between linear and nonlinear viscoelasticity. In the linear and nonlinear theory of viscoelasticity, such a task is reduced to finding creep and relaxation kernel. Creep and relaxation kernel are interconnected by a known integral relationship that establishes a relationship between stress, strain and time.The work is devoted to modeling of stress relaxation and sttrain of hereditary materials. Stress relaxation is described by a nonlinear integral equation with an Abel’s kernel. New efficient method has been proposed for determining of parameters (α, δ). Bisection method is used for obtaining of parameter α. Algorithm have been developed for calculating of parameters of α and δ.
Keywords: relaxation; bisection method; conditional instantaneous stress; relaxation stress